Determination and analysis of the price/ earnings indicator with a forecasted cash flow during during periods and with a constant annual profit of the company - O. A. Zemlyanskii (Вестник университета)
. Away for calculating and analyzing the price/earnings indicator and future value/earnings ratio of company with the predicted constant cash flow and constant annual profit of the company has been offered. The dynamic of the P/E and F/E indicators has been analyzed for various components of the calculation formula: forecast periods, rates of discount or build-up rates. The proposed way of calculating the ratio price/earnings of companies with a constant cash flow and constant annual profit for several periods allows to compare them with the value of the price/earnings indicator for one period with the projected annual profit of the company, to analyze the differences in the calculation of the price/earnings indicator for one and several periods and for different methods of calculating the discount rate.